On fundamental principles of the optimal number and location of loading bays in urban areas - Letnik, Tomislav; Peruš, Iztok; Božičnik, Stane; Mencinger, Matej (Transport, 2019)
The paper is dealing with the problem of finding the optimal number and location of Loading Bays (LBs) for efficient urban last mile deliveries. To solve the problem a multi-parametric model of the idealized urban area is introduced and applied to various instances of a rectangular urban grid structured zones. Multi-parametric approach is used to assess statistically the most relevant number and location of LBs. Computational and graphical results of the idealized model exhibit geometric patterns showing that the optimal Number of LBs (#LB) naturally tends to perfect squares. Moreover, even in case of generalized instances, at a selected number of LBs their distribution is not random but follows specific laws. The optimality is closely related to the prefixed (maximal) walking distance dmax, from the LB to the customer. Based on various simulations the existence and robustness of a descending convex dependence dmax = (#LB) is proven. The results might serve as a decision-making tool to determine the optimal number and location of LBs for any real-life city centre.